“Gestión de procesos para la generación de ventajas competitivas de las asociaciones agrícolas del cantón La Maná, provincia de Cotopaxi” - Ayala Oña, Antony Alexander (2023)
Agricultural associations play a crucial role in the local and national economy by offering extensive possibilities for self-sufficiency and growth. However, they face issues from empirical management, lack of understanding of process management's relevance, low levels of training, and the academic background of the owners. To address this matter, a research study was conducted with the objective of analyzing the process management in the agricultural associations of La Maná canton. Theoretical methods such as deductive and analytical-synthetic, as well as the empirical method of expert assessment, were employed to achieve the objective. The sample consisted of 143 members from 4 out of the 8 agricultural associations, as not all were available to respond to the survey. In total, the population universe is integrated by 206 members. The most notable results revealed an average rating of 3.14 ± 0.02 on a Likert scale for process management and 3.09 ± 0.03 for competitive advantages. These results were based on process management factors such as organization, planning, innovation, technology, and goal achievement; as well as competitive advantage factors such as cost leadership, differentiation, concentration, and adaptability. Although agricultural associations are relatively well-positioned in these aspects, the need to improve some of their processes and to develop their strengths was identified. In conclusion, it was determined that adequate planning, member involvement in problem-solving, and by considering buyer opinions have a better impact on competitive advantages. Based on the findings, recommendations were made to implement process improvements, create financing programs that benefit the associations, and promote their technological development.